2007
DOI: 10.1017/s1751731107000080
|View full text |Cite
|
Sign up to set email alerts
|

Season of birth modifies puberty in female and male goats raised under subtropical conditions

Abstract: In seasonal goats and sheep breeds, onset of puberty is modified by the season of birth. As adult does and bucks from subtropical Mexico display seasonal variation in their reproductive behaviour, this study was carried out to determine the effect of season of birth on puberty. Three groups of each sex born in January, May and October were used. During the seasons, does and bucks were weaned at an age of 30 days and offered ad libitum alfalfa hay and 100 g of commercial concentrate. In the female kids, the ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 23 publications
1
26
0
2
Order By: Relevance
“…However the typical kidding peak occurs from November to February, considering that most producers (90 %) mate their animals from June to September. The majority of producers (90 %) ignore the age that males reach puberty, whereas 10 % indicated that this occurs in the range of 5 to 10 months in line with former reports (Mellado, 2008;Delgadillo et al, 2007), an aspect to be accounted when considering breeding plans.…”
Section: Manejo Del Rebañosupporting
confidence: 71%
See 1 more Smart Citation
“…However the typical kidding peak occurs from November to February, considering that most producers (90 %) mate their animals from June to September. The majority of producers (90 %) ignore the age that males reach puberty, whereas 10 % indicated that this occurs in the range of 5 to 10 months in line with former reports (Mellado, 2008;Delgadillo et al, 2007), an aspect to be accounted when considering breeding plans.…”
Section: Manejo Del Rebañosupporting
confidence: 71%
“…Sin embargo, el momento en el que ocurren más partos es de noviembre a febrero, considerando que la mayoría de los productores (90 %) aparean a sus animales de junio a septiembre. Así mismo, la mayoría de los productores (90 %) desconocen la edad en la que los machos llegan a la pubertad; 10 % señaló que esto ocurre en el rango de los 5 a los 10 meses de acuerdo con informes anteriores (Mellado, 2008;Delgadillo et al, 2007), un aspecto que debe ser considerado cuando se habla de planes de mejoramiento.…”
Section: Phenotypic Characteristics Of the Goats In The Comarca Laguneraunclassified
“…Boer goat kids weaned during the normal breeding season (April/May) exhibit oestrus significantly earlier than those weaned in December (outside the natural season) (Greyling and Van Niekerk, 1990). Creole goat kids born in May began their ovulatory activity at an earlier age compared with kids born in January or October (Delgadillo et al, 2007). In all cases, kids attained puberty during the first breeding season after birth.…”
Section: Discussionmentioning
confidence: 90%
“…Depending on the time of the year kids are born, they experience different photoperiodic stimuli, so that age at puberty differs according to the season of birth. In northern Mexico, Creole -E-mail: zarazaga@uhu.es she-kids born in May commenced ovulatory activity at an earlier age than those born in January and October (Delgadillo et al, 2007). Papachristoforou et al (2000) observed that Damascus females born in October-November or in February attain puberty at the same time -the following autumn.…”
Section: Introductionmentioning
confidence: 99%
“…This review of literature is limited to the measurements of age of puberty (Freitas et al 2004a;Delgadillo et al 2007), age at first kidding (Abebe 2009;Lopes et al 2012), postpartum interval (Al-Hozab et al 1999;Freitas et al 2004a;Freitas et al 2004b;Abebe 2009), kidding interval (Mani et al 1996;Martin et al 2004), fertility (Abebe 2009), litter size (Alexandre et al 1999;Mellado et al 2006) and annual reproductive rate Sodiq et al 2004;Sodiq & Haryanto 2007;Elieser et al 2012;Adhianto et al 2013). A combination of two or more traits could be used as a measure of reproductive performance.…”
Section: Factors Influencing Reproductive Performance In Female Goatsmentioning
confidence: 99%